2010
DOI: 10.3233/jad-2010-100609
|View full text |Cite
|
Sign up to set email alerts
|

Interference from Heterophilic Antibodies in Amyloid-β Oligomer ELISAs

Abstract: Amyloid-β (Aβ) oligomers of different sizes and forms have recently been the focus for many Alzheimer's disease (AD) researchers. Various immunoassays have been used to detect low concentrations of these elusive Aβ species in different forms of human samples using little or no sample dilutions. However, the possibility that positive results may be caused by interference from heterophilic antibodies (HA) is often overlooked. HA, which recognize immunoglobulins from other species, are present in human plasma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 21 publications
0
48
0
Order By: Relevance
“…Xia et al (2009), using this ELISA to measure A␤ oligomer levels in plasma specimens from AD patients and control subjects, reported A␤ oligomers in 19 of 36 plasma samples from AD patients and 3 of 10 control subjects. However, as pointed out by Sehlin et al (2010), the possibility that heterophilic antibodies in the plasma samples may have resulted in a false positive signal in the study by Xia et al (2009) by crosslinking the capture and reporter antibodies was not examined. Sehlin et al (2010) found that 21 plasma samples which had tested positive with the ELISA subsequently tested negative when the assay was repeated with a diluent which blocked heterophilic antibody activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xia et al (2009), using this ELISA to measure A␤ oligomer levels in plasma specimens from AD patients and control subjects, reported A␤ oligomers in 19 of 36 plasma samples from AD patients and 3 of 10 control subjects. However, as pointed out by Sehlin et al (2010), the possibility that heterophilic antibodies in the plasma samples may have resulted in a false positive signal in the study by Xia et al (2009) by crosslinking the capture and reporter antibodies was not examined. Sehlin et al (2010) found that 21 plasma samples which had tested positive with the ELISA subsequently tested negative when the assay was repeated with a diluent which blocked heterophilic antibody activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, as pointed out by Sehlin et al (2010), the possibility that heterophilic antibodies in the plasma samples may have resulted in a false positive signal in the study by Xia et al (2009) by crosslinking the capture and reporter antibodies was not examined. Sehlin et al (2010) found that 21 plasma samples which had tested positive with the ELISA subsequently tested negative when the assay was repeated with a diluent which blocked heterophilic antibody activity. The study by Xia et al (2009) also used this ELISA to measure soluble and insoluble (guanidine HCl-extracted) A␤ oligomers in brain specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is worth noting that the variability of the results is very high among the many studies on oligomeric aggregates in CSF. Actually, in the majority of these studies, Ab and aSyn oligomers have been measured using immunometric or cytofluorimetric assay, which can give false positive results 152,159 due to the presence of interfering factors, such as heterophilic antibodies 160 , or the presence of RIPA buffer 151,153 . Therefore, the search for CSF oligomers may be very promising for the diagnosis and the comprehension of pathological pathways of neurodegenerative diseases, but a great effort is required to validate a reliable method of analysis.…”
Section: Oligomers As New Neurodegenerative Biomarkers?mentioning
confidence: 99%
“…Moreover, Sehlin et al [10] cast doubt as to whether the reported increased levels of Aβ oligomers in the CSF by Georganopoulou et al and Fukumoto et al [5,6] are true or due to the interference of the heterophilic antibodies (HA) in the detection of Aβ oligomer with ELISAs [10]. HA, i.e.…”
mentioning
confidence: 99%
“…naturally occurring human antibodies to immunoglobulins of animal origin, can be source of interference in immunometric routine assays. Sehlin et al [10] indeed studied the Aβ oligomer content with a sandwich ELISA in CSF samples from 104 individuals, and showed that the Aβ oligomer signals from the positive samples were strongly reduced when analyzed in the presence of factors blocking HA. It is worth noting that sick and hospitalized patients have higher levels of HA, so that these individuals may have an increased risk of generating a false positive response in any sandwich immunoassay [10,11].…”
mentioning
confidence: 99%